Archaic and Late Layers of Poetics of the Yakut Heroic Epic Olonkho (based on the Material of the Vilyui Expedition of 1938) - Aitalina A. Kuzmina (Научный диалог)
The article is devoted to the study of the historical poetics of the Olonkho Vilyui Yakuts. The relevance of the study is due to the need for an in-depth study of the archaic and late layers of the Yakut heroic epic based on the materials of the Vilyui expedition of 1938, with the help of which it is possible to reveal the specifics of the olonkho of the Vilyui region. The author of the article concludes that the materials of this expedition accurately reflect the peculiarities of the local tradition under consideration. The archaic stratum of olonkho is revealed, which is characterized by a ritual parenthetic song before or after the performance of the epic, the preservation of the mythologeme of the creation of the world, the image of the sacred birch Aar Kuduk Khatyng, a less developed description in the epic beginning. It has been established that the formation of the late layer of olonkho poetics is associated with a number of reasons, including the following: the cumulative nature of the characters’ actions under the influence of a fairy tale; demythologization; replacement of the heroic with everyday life; reflection of the negative consequences of the development of society; the appearance of borrowed words, the names of Russian cities, Christian concepts, images of Russian girls, the fire-breathing Serpent Gorynych, Baba Yaga as a result of close ties with Russians, their culture and worldview; the emergence of a war motive between the aiyy and abaasy tribes as a reflection of the Great Patriotic War; the image of the achievements of technical progress (in particular, the steamer); displacement of images; using the image of a shaman; the introduction of an intermediate layer of images of semi-ayy and semi-baasy.